El Salvador - Cummins, Ronnie; Welch, Rose (Milwaukee : Gareth Stevens Children's Books, 1990)
Presents the life of a twelve-year-old boy and his family in El Salvador, describing his home and school activities and discussing the history, geography, ethnic composition, natural resources, languages, government, religions, culture, and economics of his country.
Includes index.
Keywords: Children -- El Salvador -- Juvenile literature; Family life -- El Salvador; El Salvador -- Social life and customs.erature.; El Salvador